Evaluation of consensus method for the culture of Burkholderia pseudomallei in soil samples from Laos [version 2; referees: 2 approved] - David A.B. Dance; Michael Knappik; Sabine Dittrich; Viengmon Davong; Joy Silisouk; Manivanh Vongsouvath; Sayaphet Rattanavong; Alain Pierret; Paul N. Newton; Premjit Amornchai; Vanaporn Wuthiekanun; Sayan Langla; et al. (Wellcome Open Research, 2018)
Background: We have previously shown that PCR following enrichment culture is the most sensitive method to detect Burkholderia pseudomallei in environmental samples. Here we report an evaluation of the published consensus method for the culture of B. pseudomallei from Lao soil in comparison with our conventional culture method and with PCR with or without prior broth enrichment. Methods: One hundred soil samples were collected from a field known to contain B. pseudomallei and processed by: (i) the conventional method, (ii-iii) the consensus method using media prepared in either Laos or Thailand, and (iv) the consensus method performed in Thailand, as well as by (v) PCR following direct extraction of DNA from soil and (vi) PCR following broth pre-enrichment. Results: The numbers of samples in which B. pseudomallei was detected were 42, 10, 7, 6, 6 and 84, respectively. However, two samples were positive by the consensus method but negative by conventional culture, and one sample was negative by PCR following enrichment although B. pseudomallei was isolated by the conventional culture method. Conclusions/Discussion: The results show that no single method will detect all environmental samples that contain B. pseudomallei. People conducting environmental surveys for this organism should be aware of the possibility of false-negative results using the consensus culture method. An approach that entails screening using PCR after enrichment, followed by the evaluation of a range of different culture methods on PCR-positive samples to determine which works best in each setting, is recommended.